A phytopharmacological review on an important medicinal plant - Wrightia tinctoria - Dixit, Ashish; Jain, A K; Tiwari, Pawan; Gupta, Nidhi; Gangele, Priyanka (Current Research in Pharmaceutical Sciences, 2014)
There are variety of plants are present which have applications due to their medicinal values. Wrightia tinctoria is a member of the family Apocynaceae. It is small to medium-size deciduous tree. This plant grows up to 18 m tall and to 20 cm with green marks on the stem and producing milky-white resin. The bark of this plant is smooth, somewhat corky and pale grey. Traditionally Wrightia tinctoria commonly called as "Jaundice curative tree" in south India. This plant possesses high medicinal value. The Wrightia tinctoria is used for the treatment of several diseases including very severe disease like aids and cancer. In this review we want to highlight on different parameters of plant like general description and distribution, microcopy, chemical constituents and traditional uses with special emphasis of pharmacological action like analgesic, antiinflammatory, anthelmintic, antiulcer, antidiabetic, anticancer, and antipyretic and antidysentric activity. This plant is also used in the treatment of skin diseases like psoriasis and as indigo dyes. The whole study gives information to aware the herbal era remedy for development of new development.